2003
DOI: 10.1038/sj.bjc.6600973
|View full text |Cite
|
Sign up to set email alerts
|

Latest trends in cancer incidence among UK South Asians in Leicester

Abstract: Using cancer registry data, we show that although South Asians have lower rates of cancer than the rest of the population, this is changing with age and time. Younger South Asians, particularly children, are at increased risk. While generally cancer rates have fallen over the last decade, they are increasing among South Asians. Cancer incidence rates in the UK have been reported to be much lower for South Asians (Indian, Pakistani and Bangladeshi) than the rest of the population (Winter et al, 1999). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
49
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 3 publications
6
49
0
Order By: Relevance
“…Over the period 1986 -1994, there was an increase in the number of registered South Asian patients with breast cancer. These results are consistent with other studies, showing increased incidence rates of breast cancer in South Asian women over time, while the rates decreased among non-Asian population Dos Santos Silva et al, 2003;Smith et al, 2003). These changes could be explained by the ageing population of South Asians, increased proportion of secondgeneration immigrants and significant differences in lifestyle and other exposures occurring in South Asian minority population in the UK.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Over the period 1986 -1994, there was an increase in the number of registered South Asian patients with breast cancer. These results are consistent with other studies, showing increased incidence rates of breast cancer in South Asian women over time, while the rates decreased among non-Asian population Dos Santos Silva et al, 2003;Smith et al, 2003). These changes could be explained by the ageing population of South Asians, increased proportion of secondgeneration immigrants and significant differences in lifestyle and other exposures occurring in South Asian minority population in the UK.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is likely to reflect the generally younger age of ethnic minorities in Britain (Office for National Statistics, 1996). It is consistent with observations in ethnic minority groups both in the UK and the USA (African-American women) (Coates et al, 1992;Elmore et al, 1998;Joslyn and West, 2000;Dos Santos Silva et al, 2003;Smith et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The biggest minority population (25.7%) was described in the census as Indian, although some of these people would use a different name such as African/Asian to describe their origin. It has been predicted that by 2011, 50% of the population of Leicester will be of Asian origin (Rex, 1999).Cancer registration statistics collected between the start of 1990 and the end of 1999 for the city of Leicester showed that South Asian patients had a lower cancer incidence than non-South Asians (Smith et al, 2003a). When adjusted for age and socioeconomic deprivation, incidence rate ratio (IRR) was 0.61 for male and 0.75 for female population.…”
mentioning
confidence: 99%
“…Cancer registration statistics collected between the start of 1990 and the end of 1999 for the city of Leicester showed that South Asian patients had a lower cancer incidence than non-South Asians (Smith et al, 2003a). When adjusted for age and socioeconomic deprivation, incidence rate ratio (IRR) was 0.61 for male and 0.75 for female population.…”
mentioning
confidence: 99%